Does the world real interest rate affect the real exchange rate? The South East Asian experience - Karine Gente; Miguel A. León-Ledesma (University of Kent, Department of Economics, 2004)
We analyse the consequences of US real interest rate rises on the real exchange rate (RER) in a two-good overlapping generations model of a semi-small open economy. The equilibrium RER depreciates (appreciates) when the world interest rate increases in a debtor (creditor) country. We then study empirically the reaction of the RER in a set of South East Asian (SEA) countries to shocks in US real interest rates. The results support the conclusions of the theory model at least for Singapore, Thailand and South Korea during the period 1980-2001.
Keywords: D91; F31; F41; 330; Real exchange rate; overlapping generations; world interest rate shock; Realzins; Kaufkraftparität; Overlapping Generations; Schätzung; USA